Skin flap pattern in skin cancer at Sanglah General Hospital Denpasar, Bali-Indonesia - Made Wardhana; IGN Darmaputra; I Gde Nengah Adhilaksman Sunyamurti Wirawan; Nyoman Yoga Maya Pramita; Rikcy Fernando Maharis; Ni Made Dwi Puspawati; IGAA Dwi Karmila; IGAA Praharsini (DiscoverSys Inc., 2019)
Background: The prevalence of skin cancer is consistently increasing recently, an hence a more comprehensive management is necessary for patients’ satisfaction. Generally, skin cancer is categorized into several histological types, including melanoma, basalioma, squamous cell carcinoma (SCC), and several other less common types such as keratoacanthoma, pyogenic granuloma, and Bechet disease. In dermatology, the intervention is limited which only consists of infiltrative anesthesia, no involvement of other organs, and no attachment to the underlying tissue. Therefore, random skin flap frequently becomes the preferred option that involves advancement, rotation, transposition, and interpolation flap. This study aims to investigate the profile of skin cancer and flap pattern among patients undergoing skin flaps procedure at Dermatology and Venereology Department of Sanglah General Hospital, Denpasar. Method: This study included all skin cancer patients who underwent skin flap surgery. Samples collection was performed retrospectively using patients’ medical records from January 2015 - December 2018. Results: Over the study period, there were a total of 41 skin cancer patients who underwent skin flap surgery of whom 10 (54.6%) patients were diagnosed with melanoma, 16 patients with basalioma, 9 patients with SCC and the remaining included 3 cases of acanthoma and 1 Bechet disease. Regarding the flap types, simple advancement and its variances were performed in 6 melanoma, 11 basaliomas, 5 SCC and 4 keratoacanthoma cases. Transposition flap was performed in 2 melanoma, 3 basalioma, and 3 SCC cases; whereas rotation flap was performed in 2 melanoma and 2 basaliomas and SCC cases.Conclusion: From 41 skin cancer patients discovered, basalioma was the most frequent cases and advancement techniques were the most frequently performed flap surgery. Only 1 post-surgical infection was found after rotational flap procedure.